Mapping Scientific Literature on Mental Health and Depression in Football Players: Insights from a Scopus Bibliometric Analysis - Aji Sukma, Benny; Pamungkas, Hari; Nidomuddin, Muhammad (PT FORMOSA CENDEKIA GLOBAL, 2025)
Mental health problems, like depression, are now seen as major issues for football players because of the mental stress and physical challenges of the sport. This study will use bibliometric methods to map out and study worldwide research trends on mental health and depression in football players from 2015 to 2025. A bibliometric analysis was done using the Scopus database. The data was analyzed with VOSviewer and R-studio software to study performance and map out the science, including looking at who wrote together, how often keywords appeared together, and how often articles were cited. This bibliometric study gives a full picture of research activity on mental health and depression in football players.